Role of Valganciclovir in Children with Congenital CMV Infection: A Review of the Literature - Davide Pata; Danilo Buonsenso; Arianna Turriziani-Colonna; Gilda Salerno; Lucia Scarlato; Lara Colussi; Rolando Ulloa-Gutierrez; Piero Valentini (MDPI AG, 2023)
Background: Cytomegalovirus (CMV) is the most common agent of congenital infection in humans. It is a main cause of neurodevelopmental delay and sensorineural hearing loss in infancy. Since the 2000s, a number of studies have used Valganciclovir as a therapy for children with congenital CMV infection. Methods: In order to evaluate the efficacy of Valganciclovir in preventing clinical sequelae and its possible side effects, we performed a review of the published literature. This search was completed via PubMed for manuscripts published from January 2007 to December 2021, combining the MeSH words "Valganciclovir", "Congenital", and "Cytomegalovirus". Results: A total of 27 articles were included (12 retrospective studies, 4 prospective studies, 1 randomized controlled trial, and 10 case reports). The clinical features were similar to those already described in the literature. The therapeutic protocols used were very different between the various studies included and neonatal antiviral treatments were only moderately effective. The therapy proved to be well-tolerated. Conclusions: The quality of the included studies and the sample size were limited due to the rarity of the disease. The use of different therapeutic protocols in terms of starting dates, doses, and durations made it impossible to compare and correctly evaluate the efficacy of the treatments. Randomized controlled trials are needed to establish the correct effective dose with the fewest side effects and the most efficient duration of therapy.